The use of carbogen for interruption of febrile seizures - the randomized controlled CARDIF trial - Claudia Weiß; Alice Hucko; Stephanie Müller-Ohlraun; Stefanie Märschenz; Peter Martus; Dietmar Schmitz; Markus Schuelke (PLoS ONE, 2025)
Febrile seizures are the most common seizure disorders in children. Fever-induced hyperventilation and subsequent hypocapnia may precipitate febrile seizures. In preclinical studies and in individual children, increasing CO 2 partial pressure has shown potential to terminate febrile seizures. We hypothesized that the use of carbogen (5% CO 2 plus 95% O 2 ) in the home environment would be an effective and safe treatment for recurrent febrile seizures. The CARDIF (CARbon DIoxide against Febrile seizures) trial is a randomized, monocentric, prospective, double-blind, placebo-controlled, crossover study to determine whether short-term inhalation of carbogen in the home environment can stop febrile seizures. 100% oxygen was used as a placebo control. We included children aged 0.5 to 5.0 years who presented after a first febrile seizure in the absence of severe organ or neurological disease, pathological EEG changes, or a history afebrile seizures. We noted parent-reported seizure duration, benzodiazepine use, and any serious adverse events. We enrolled n = 92 patients. In n = 20 children, at least one recurrent febrile seizure was treated with either carbogen or oxygen . Six of these children received both carbogen and oxygen in a planned crossover design. The febrile seizure was terminated in 5/15 episodes on carbogen and in 8/11 episodes on oxygen (Fischer’s exact test; p = 0.11). Children with ≥2 recurrent febrile seizures completed the crossover arm. In these children, febrile seizures stopped during carbogen administration in 3/6 cases and during oxygen administration in 5/6 cases. In conclusion, carbogen did not interrupt acute febrile seizures more often than placebo . Home caregivers had difficulty determining when a seizure had stopped. Trial registration ClinicalTrials.gov NCT01370044